Drone Up! Quantifying Whale Behavior From a New Perspective Improves Observational Capacity - Torres, Leigh G.; Nieukirk, Sharon L.; Lemos, Leila; Chandler, Todd E. (Frontiers in Marine Science, 2018)
From our traditional boat-based horizontal perspective, marine megafauna behavioral observations are typically limited to animal surfacings. Achieving an aerial perspective has been restricted to brief helicopter or airplane based observations that are costly, noisy and risky. The emergence of commercial small unmanned aerial systems (UAS) has significantly reduced these constraints, and provide a stable, relatively quiet and inexpensive platform that enables replicate observations for prolonged periods with minimal disturbance. The potential of UAS for behavioral observation appears immense, yet quantitative methods of video analysis and proof of utility as an observational tool are required. We use UAS footage of gray whales foraging in coastal waters of Oregon, USA to develop analysis methods, assess behavioral impacts caused by UAS, determine the change in observation time enabled by UAS, and describe unique behaviors observed via UAS. Boat-based behavioral observations from 53 gray whale sightings between May and October 2016 were compared to behavioral data extracted from video analysis of UAS flights during those sightings. We used a DJI Phantom 3 Pro or 4 Advanced, recorded video from an altitude ≥25m, and detected no behavioral response by whales to the UAS. Two experienced whale ethologists conducted UAS video behavioral analysis, including tabulation of whale behavior states and events, and whale surface time and whale visible time (total time the whale was visible including underwater). UAS provided three times more observational capacity than boat-based observations alone (300 vs. 103 minutes). When observation time is accounted for, UAS data provided greater observations of all primary behavior states (travel, forage, social, rest) relative to boat-based data, especially forage, which increased by three times. Furthermore, UAS enable documentation of multiple novel gray whale foraging tactics (e.g., headstands: n=58; side-swimming: n=17; jaw snapping and flexing: n= 10) and 33 social events (nursing, pair coordinated surfacings) not identified in the field. This study demonstrates the significant added value of UAS to marine megafauna behavior and ecological studies. With technological advances, robust study designs, and effective analytical tools, we foresee increased UAS applications to marine megafauna studies to elucidate foraging strategies, habitat associations, social patterns, and response to human disturbance.